Best Practices of Promoting a Positive School Learning Climate among Principals of Cluster Secondary Schools Towards Realization of Education Blueprint 2013-2025 Malaysia - Salleh, Mohamad Johdi; Hatta, Muhammad (Advances in Social Sciences Research Journal, 2018)
The purpose of the study was to investigate the best practices of promoting a positive school learning climate among principals of Cluster Secondary Schools Malaysia according to principals’ and teachers’ perceptions. The Principal Instructional Management Rating Scale (PIMRS) modified by Hallinger and Murphy (1987), Latip (2006), Hatta (2010), Surayya (2016) was used as the data collection instrument through survey questionnaire. There were 871 respondents of different genders, ethnics, type of schools, and, position of responsibilities at schools were participated. The result of the study shows that the highest score was on dimension ‘Developing and Enforcing Academic Standards’ with mean 4.290 and standard deviation 0.814. It was followed respectively by ‘Providing Incentives for Learning’ mean 4.060 and standard deviation 0.904; ‘Protecting Instructional Time’ mean 3.855 and standard deviation 0.963 and ‘Providing Incentives for Teachers’ mean 3.607 and standard deviation 1.095. Meanwhile, the two best statements practiced by the principals were ‘Use assemblies to honor students for their academic work and/or behavior in classroom’ mean 4.39 and ‘Encourage teachers to start class on time and teach to the end of the period’ mean 4.38. It is hoped that this study will provide useful findings which will effectively assist the process of promoting a positive school learning climate among principals and teachers of secondary schools. Consequently, facilitate and improve students’ academic performance in achieving the first class human capital who compatibly excellent nationally and internationally as stipulated in the purpose of establishing the Cluster Secondary schools by the Ministry of Education towards realization of Vision 2020 and the Education Blueprint 2013-2025 Malaysia.